2009
DOI: 10.1111/j.1755-263x.2009.00059.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon payments as a safeguard for threatened tropical mammals

Abstract: One reason for the rapid loss of species-rich tropical forests is the high opportunity costs of forest protection. In Kalimantan (Indonesian Borneo), the expansion of high-revenue oil palm (Elaeis guineensis) plantations currently threatens 3.3 million ha of forest. We estimate that payments for Reduced Emissions from Deforestation and forest Degradation (REDD) could offset the costs of stopping this deforestation at carbon prices of US$10-33 per tonne of CO 2 , or $2-16 per tonne if forest conservation target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
100
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(107 citation statements)
references
References 20 publications
6
100
0
1
Order By: Relevance
“…First, most previous studies have relied upon a deterministic "opportunity cost" assumption that deforestation would be avoided entirely wherever potential carbon payments exceed net revenue from alternative land uses (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). In contrast, we calibrate the marginal impact of potential carbon payments on deforestation using the empirical relationship between the pattern of observed deforestation in a historical period and spatial variation in the benefits and costs of converting land from forest to agriculture.…”
mentioning
confidence: 99%
“…First, most previous studies have relied upon a deterministic "opportunity cost" assumption that deforestation would be avoided entirely wherever potential carbon payments exceed net revenue from alternative land uses (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). In contrast, we calibrate the marginal impact of potential carbon payments on deforestation using the empirical relationship between the pattern of observed deforestation in a historical period and spatial variation in the benefits and costs of converting land from forest to agriculture.…”
mentioning
confidence: 99%
“…Yet without specific provisions for biodiversity, REDD is likely to protect forests that are most cost-effective for reducing carbon emissions [29]. O. Venter et al [30] have demonstrated that prudent targeting of REDD funds can double biodiversity benefits while incurring only a small reduction (4% to 8%) in carbon benefits. There are however challenges in developing equitable benefit sharing mechanisms at different scales and would require adoption of pro-poor approach that is central to development of community-based approaches to forest management [31].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, forest degradation because of selective logging, fuel wood collection, or grazing of animals also brings benefits, and avoiding this degradation foregoes these benefits (Pagiola and Bosquet 2009). These opportunity costs are usually the single most important category of costs a country would incur if it reduced its rate of forest loss to secure payments for ecosystem services (Venter et al 2009b). An open market system, in which all economic actors have an equal opportunity of entry in that market, would require that the forest manager understands how the opportunity costs of foregone deforestation develop over time in order to weigh up whether forest protection for ecosystem services remains an economically competitive option.…”
Section: Monitoring and Verification Challengesmentioning
confidence: 99%